Influences of a Migration Background on Daily Urban Mobility - Welsch, Janina; Conrad, Kerstin; Wittowsky, Dirk; Reutter, Ulrike (Raumforschung und Raumordnung | Spatial Research and Planning, 2014)
Germany is facing substantial demographic changes. Beside ageing and shrinking there is a growing ethnic diversity due to past and ongoing migration. Migrants and their offspring (people with a migration background) account for a noticeable and growing share of the population. Despite these developments, only very few German transport studies focussed so far on migrants and their mobility behaviour. Therefore, this study examines the mobility behaviour of people with and without a migration background in Offenbach am Main. The results show differences for various mobility indicators such as driving licence, numbers of cars and bicycles per household, cycling ability and the use of different transport modes. Additional multivariate analyses show the main influencing factors for transport mode use. Thus, the study extends the spare empirical knowledge of migrants and their daily urban mobility in Germany.